Dynamics of the development of objective index methods for assessing the hygiene condition of removable dentures (literature review) - Kurylo Володимир Олександрович; Korol Дмитро Михайлович (Actual Dentistry, 2024)
Resume. A study was conducted on the use of index methods for assessing the hygiene of removable orthopedic dental structures. The work is based on the study and comprehensive analysis of educational and methodological and scientific literature, as well as patent practice, dedicated to the problem of index assessment of the hygiene of removable dental orthopedic dental structures. The purpose of the work is to study the dynamics of the development of objective methods for assessing the hygienic condition of removable dental orthopedic structures. Patent information search was conducted in the digital databases of the platforms «Scopus», «Pub Med», and the Scientific Electronic Library of Periodicals of the National Academy of Sciences of Ukraine in order to achieve the goal. The research presents an analytical review of the literature. The search and main selection of materials of original literary sources was carried out using key words. Processed, including 50 identified and analyzed sources. Among them can be distinguished 30 domestic and 20 foreign sources. The search depth is 61 years. 15 methods of index assessment of the hygiene of removable orthopedic dental structures are presented in chronological order. Their advantages and disadvantages are analyzed and described. As a result of the analysis of special literature, a corresponding conclusion was formulated based on the results of the research. Objective index assessment of the hygienic condition of the oral cavity and removable dental prostheses is relevant. In order to prevent pathological processes that occur after the application of removable orthopedic structures to the supporting tissues of the prosthetic bed and their subsequent use by the patient, a quick and convenient, objective and accurate assessment of the hygienic state of the oral cavity in general and removable orthopedic structures in particular is important in the dynamics of clinical observations using different indexes. This study is a fragment of the NDR of the Department of Propedeutics of Orthopedic Stomatology of the Poltava State Medical University «Ways of practical implementation of digital technologies for the diagnosis and treatment of secondary adentia», state registration number 0121U113861.